INCREASING ABILITY OF SPEAKING IN JAVANESSE LANGUAGE BY PLAYING KETHOPRAK - Nanik Herawati (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
Lesson of Javanesse Language being practised in State Senior High School (SMA) in Klaten has purposes that students have ability and habit speaking with Javanesse language correctly in many situation. One of the ways to increase the ability of speaking Javanesse language is by playing kethoprak. This media can mediate and simplify an activity to achieve the goal. Playing kethoprak is one of the media where the students do the activity in the classroom by perfoming kethoprak with certain theme. The Javanesse language can be classified into two groups: (1) Basa Ngoko ‘impolite language’ and (2) Basa Krama ‘polite language’. The problem formulation is: can playing kethoprak increase the ability of speaking Javanesse language of students of SMA in Klaten? The objective of this reseach is to know whether playing kethoprak can enhance the ability of speaking Javanesse language. This reseach uses the design of class action. The data collection technique is done by observation, questions, and notes. The data will be analysed with descriptive technique, that is, by describing the increasing ability of speaking Javanese. The speaking ability can be valued after the students make the scenario and perform the kethoprak. The increasing of the ability is reviewed in lexicon choice of Basa Ngoko and Basa Krama. Before performing the drama, the lexicon choice has many mistakes. But after performing the drama twice or three times, the mistakes in lexicon choice decreases.